Media Convergence and Diversification – The Meeting of Old and New Media. (2015) - Arsenijević, Jasmina; Andevski, Milica
Abstract: The aim of this study is to examine new media competencies of the members of the Serbian academic community in relation to their digital participation (Facebook, Twitter, YouTube, forums and message boards). The questionnaire has a high representativeness coefficient of KMO=.90, while the questionnaire as a whole has a high reliability of .91. The results indicate that there is a significant correlation between the respondents' digital participation and almost all NML components. The greatest contribution of this study is in overcoming the empirical and theoretical dilemmas about the relationship and interactions between the modern man and social networks within the digital environment. Our research shows that there is a positive correlation between the respondents' participation in digital social networks and new media literacy.